La crisis del Prestige en la prensa vasca desde una concepción medioambiental - Odriozola Chéné, Javier (Estudios sobre el Mensaje Periodístico, 2010)
This study examines the behavior of two Basque newspapers (El Correo Español y Deia) before the environmental disaster caused by the ship Prestige. The objective is to see how both newspapers, don’t have an established strategy on these issues. Thus, they face many difficulties in carrying out a proper depth in key aspects of the crisis. Through content analysis, we examine the various reports appeared in the newspapers. We rely on this analysis and journalistic routines to retake the path taken by journalists when reporting on this event.
Keywords: Analysis content; Newsmaking; Environmental journalism